Themes in Information-Rich Functional Programming for Internet-Scale Data Sources - Syme, Don; Takeda, Kenji; Malayeri, Donna and (ACM, 2013)
The F# language includes a feature called “F# 3.0 Type Providers” to support the integration of internet-scale information sources into a strongly typed functional-first programming envi-ronment. In this position paper we describe the key themes in information-rich functional programming that we have observed during this work. Our contribution is to document these themes and highlight future challenges and opportunities, in the context of a recently released, practical, open-source system for information-rich functional programming. We believe that this area is rich in excellent opportunities for future language and tooling research, information-space integration and schematization techniques.